2022
DOI: 10.3390/ijerph191811746
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of a Public Health Approach to Improving the Physical Health of People Living with Mental Illness

Abstract: With already wide disparities in physical health and life expectancy, COVID-19 presents people with mental illness with additional threats to their health: decreased access to health services, increased social isolation, and increased socio-economic disadvantage. Each of these factors has exacerbated the risk of poor health and early death for people with mental illness post-COVID-19. Unless effective primary care and preventative health responses are implemented, the physical illness epidemic for this group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…It may be possible that mothers with pre-existing mental health disorders are more medically complicated in general, 40 42 thereby increasing overall risks for complications postpartum especially after PPH. 43,44 As previously mentioned, these patients are at increased risk for obesity 45 which itself increases maternal risks due to cardiovascular diseases, thromboembolism, hypertension, and stroke. 46 48 Our study was unable to account for obesity as body mass index was not consistently available in the TriNetX ® database.…”
Section: Discussionmentioning
confidence: 94%
“…It may be possible that mothers with pre-existing mental health disorders are more medically complicated in general, 40 42 thereby increasing overall risks for complications postpartum especially after PPH. 43,44 As previously mentioned, these patients are at increased risk for obesity 45 which itself increases maternal risks due to cardiovascular diseases, thromboembolism, hypertension, and stroke. 46 48 Our study was unable to account for obesity as body mass index was not consistently available in the TriNetX ® database.…”
Section: Discussionmentioning
confidence: 94%
“…Some authors have suggested that the existing inequalities between people with schizophrenia and the general population have increased even further as a result of the pandemic 48 . COVID-19 has increased the prevalence of physical health problems and the risk of premature death in people with severe mental disorders, resulting in increased physical health disparities in people living with mental illness 49 …”
Section: Discussionmentioning
confidence: 99%
“… 48 COVID-19 has increased the prevalence of physical health problems and the risk of premature death in people with severe mental disorders, resulting in increased physical health disparities in people living with mental illness. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extant literature tends to over-emphasize individual health responsibilities at the expense of social factors that influence health status. The purpose of this literature review was to (1) distill consumer experiences, perspectives, and understandings concerning their physical and mental health and (2) ascertain the role of consumers in the design of research and across all aspects of the research production process.…”
Section: Introductionmentioning
confidence: 99%
“…As a group, people with a lived experience of mental health concerns have far worse health and life expectancy outcomes than the rest of the population ( 1 ). Mental health consumers experience two times the rate of early death compared to the general population, and in rural Australia, this rate is three times higher ( 2 ) 1 .…”
Section: Introductionmentioning
confidence: 99%